2016
DOI: 10.1080/14656566.2016.1209486
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine dosing choices in specific populations: review of expert opinion

Abstract: There was general agreement that treatment outcomes can be improved by optimising buprenorphine doses in specific subgroups. Specific groups in whom buprenorphine doses may be too low and who could have better outcomes with optimised dosing were identified on the basis of clinical practice experience. These groups include people with severe addiction, high tolerance to opioids, and psychiatric comorbidities. In these groups it is recommended to review dosing choices to ensure buprenorphine dosing is sufficient. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…This study also did not record the patients’ comorbidities, which may substantially affect individual dosages and outcomes (10). The clinic does not provide treatment on comorbidities, as patients are usually referred to their general practitioner when health problems arise, so data were not available in a format which could have been used for this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also did not record the patients’ comorbidities, which may substantially affect individual dosages and outcomes (10). The clinic does not provide treatment on comorbidities, as patients are usually referred to their general practitioner when health problems arise, so data were not available in a format which could have been used for this study.…”
Section: Discussionmentioning
confidence: 99%
“…A sufficient dose to dissolve heroin craving is the key element to the success of opioid maintenance (9, 10). Methadone is often used in dosages around 50–100 mg daily, and buprenorphine in dosages above 8 mg/day is effective in reducing heroin craving (11).…”
Section: Introductionmentioning
confidence: 99%
“…The antipsychotic effectiveness of opioid agonists is highlighted in a recent review, in which it is suggested that the use of opioid agonists deserves reconsideration because of their anticraving capability and effectiveness on the psychopathological level [ 40 ]. It has also been stated that specific groups, including patients with psychiatric comorbidities, may benefit from optimized and higher doses of buprenorphine to ensure sufficient dosing [ 41 ]. It is relevant to combine antipsychotic and opioid agonist medications with psychosocial support [ 38 ], since group counselling, contingency management and long-term residential treatment have been shown to have positive effects [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The toxic properties of fast-acting opiates and the therapeutic properties of slow-acting ones prove to be crucial issues in HUD patients, whether they do or do not have DD. Methadone and buprenorphine should be recognized as psychoactive medications, with useful properties in the treatment of opiate addiction, having a wider therapeutic potential when heroin addiction is combined with a psychiatric disorder [20,49,57,59,61,[63][64][65][66][67][68][69][70][71][72][73].…”
Section: Towards a Hierarchical Approach To Dual Disorder Treatmentmentioning
confidence: 99%